Research of the statistical control method for automatic control of printing process - Левыкин, Игорь Викторович; Бойко, Екатерина Викторовна (Eastern-European Journal of Enterprise Technologies, 2012)
Nowadays the issue of printed matter of high quality is one of the urgent topics. Almost each printer has to solve the problems of the production quality, research implementation, examination and optimization of the equipment and materials, and to study the market demands. To increase the competitiveness the national enterprises should improve or to create and implement, if necessary, the system of quality estimation of printed matter, which would conform to the requirements of international, national and trade standards. The quality of printed matter is considered nowadays the determinative for its competitiveness at home and foreign market. The article concerns the research of statistic methods of control of the quality of printing on the on the offset equipment. On the basis of the research the criteria that influence the quality of printing were considered. With statistic control of two the most important criteria of defects emergence we determined and analyzed the choice of materials and the setup of printing equipment